2003
DOI: 10.1007/s00438-003-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Instability of short-sequence DNA repeats of pear pathogenic Erwinia strains from Japan and Erwinia amylovora fruit tree and raspberry strains

Abstract: An array of short-sequence DNA repeats (SSRs) occurs in the plasmid pEA29 of the fire blight pathogen Erwinia amylovora. A large number of ''fruit tree'' strains, mainly from Central and Western Europe, were screened for their SSR numbers, and the analyses were extended to five raspberry strains from North America and six pear pathogenic Erwinia strains from Japan. The repeat ATTACAGA present in all E. amylovora strains was found to be reiterated 3 to 15 times. The Japanese strains contained the major repeat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
2
19
1
Order By: Relevance
“…However, our results support the assumption that most Italian E. amylovora strains isolated in the Po valley originated from infected plant material from Belgium (Zhang et al 1998;Jock et al 2002). In fact, nearly all Italian strains used in this study had SSR numbers of four to six SSR units similar to strains from Belgium (Jock et al 2003). Therefore, strain UniBaBA6 with eight SSR units and isolated from Apulia region in southern Italy, might have another origin.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…However, our results support the assumption that most Italian E. amylovora strains isolated in the Po valley originated from infected plant material from Belgium (Zhang et al 1998;Jock et al 2002). In fact, nearly all Italian strains used in this study had SSR numbers of four to six SSR units similar to strains from Belgium (Jock et al 2003). Therefore, strain UniBaBA6 with eight SSR units and isolated from Apulia region in southern Italy, might have another origin.…”
supporting
confidence: 85%
“…UK (Jock et al 2003). No other isolates were found in Europe with this specific number of SSR units.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…A disadvantage of this technique is that SSRs were described as unstable entities that undergo frequent variation in length because of slipped strand mispairing during DNA synthesis [7,8,11]. However, our results showed that SSR numbers of several strains remained constant under laboratory conditions.…”
Section: Discussionmentioning
confidence: 60%
“…possible. However, without this additional knowledge traceability is very difficult and probably impossible for strains with common SSR numbers of 5 or 6 [11]. For strains in culture collections the differentiation into PFGE-type (Pt1 to Pt6) and SSR-type (SSR-3 to SSR-15) represents a valuable tool for strain classification.…”
Section: Discussionmentioning
confidence: 99%